2021
DOI: 10.1007/s00125-021-05498-0
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin reduces thrombin generation and platelet activation: implications for cardiovascular risk reduction in type 2 diabetes mellitus

Abstract: Aims/hypothesis People with diabetes have an increased cardiovascular risk with an accelerated development of atherosclerosis and an elevated mortality rate after myocardial infarction. Therefore, cardioprotective effects of glucose-lowering therapies are of major importance for the pharmacotherapy of individuals with type 2 diabetes. For sodium–glucose cotransporter 2 inhibitors (SGLT2is), in addition to a reduction in blood glucose, beneficial effects on atherosclerosis, obesity, renal function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…We also observed enrichment of platelet signaling, activation, and aggregation involving ALB, PIK3R, and TIMP1 from shortest paths analysis. This result is convergent with a study showing that dapagliflozin-mediated atheroprotection in mice is driven by ameliorated thrombin–platelet-mediated inflammation and elevated HDL-cholesterol ( Kohlmorgen et al, 2021 ). Additionally, analysis using the KEGG pathway database pointed out influence of the extended SGLT2 network on processes related to neuroactive ligand–receptor interaction and pathways in cancer.…”
Section: Discussionsupporting
confidence: 88%
“…We also observed enrichment of platelet signaling, activation, and aggregation involving ALB, PIK3R, and TIMP1 from shortest paths analysis. This result is convergent with a study showing that dapagliflozin-mediated atheroprotection in mice is driven by ameliorated thrombin–platelet-mediated inflammation and elevated HDL-cholesterol ( Kohlmorgen et al, 2021 ). Additionally, analysis using the KEGG pathway database pointed out influence of the extended SGLT2 network on processes related to neuroactive ligand–receptor interaction and pathways in cancer.…”
Section: Discussionsupporting
confidence: 88%
“…In the cardiovascular system, in infarcted rat hearts, dapagliflozin treatment after infarction increases myocardial M2 macrophage polarization with a concomitant decrease in M1 via acute-phase response factor (STAT3) signaling, a well-known key factor in the polarization of M2, contributing to attenuate cardiac fibrosis [ 168 , 169 ]. In apolipoprotein E-deficient (ApoE −/− ) mice with T2DM induced with streptozotocin (STZ), dapagliflozin treatment can attenuate atherosclerosis lesions and decrease atherosclerotic macrophage infiltration [ 170 , 171 ], an effect also observed in ApoE −/− mice fed with a high-fat diet [ 172 ], in a normoglycemic rabbit model of atherosclerosis [ 173 ], in LDL-receptor-deficient (Ldlr −/− ) mice with a high-fat and high-sucrose diabetogenic diet [ 174 ], or in T2DM rats [ 175 ]. Moreover, in mice with abdominal aortic aneurysms, dapagliflozin reduces the risk and progression of small aneurysms in part by attenuating aortic wall macrophage infiltration [ 176 ].…”
Section: Sglt2i and Inflammationmentioning
confidence: 99%
“… 33 Another sodium‐glucose cotransporter 2 inhibitor, dapagliflozin, is reported to mediate the proposed athero‐protective effects of elevated HDL and to ameliorate thrombin‐platelet‐mediated inflammation. 34 We found that a possible inflammatory marker of HDL/CRP ratio had significant prognostic importance among lower LVEF patients with HFpEF.…”
Section: Discussionmentioning
confidence: 70%